2018
DOI: 10.1177/0011128718800286
|View full text |Cite
|
Sign up to set email alerts
|

Do We Have It All Wrong? The Protective Roles of Peers and Criminogenic Risks From Family During Prison Reentry

Abstract: Prior work on the process of reentry from prison has highlighted the pivotal role that family and peers play during reintegration. Families are traditionally understood as important protective mechanisms against recidivism whereas peers are typically viewed as primarily criminogenic. Yet, drawing from differential coercion and social support theory, family and peer relationships can both be supportive (and protect against recidivism) and coercive (and contribute to recidivism). Using four waves of data from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 43 publications
(79 reference statements)
1
26
0
Order By: Relevance
“…In a study published earlier this year entitled, "Do We Have it All Wrong? ", we found that after accounting for family support, family conflict, peer support, and peer crime, our major assumptions about family and peers were completely in opposite direction as would currently be assumed (Mowen & Boman, 2019b). After accounting for the multifaceted roles of both family and peers among a sample of returning persons, we found that family conflict promoted crime while peer support reduced it!…”
Section: Empirical Studiesmentioning
confidence: 65%
“…In a study published earlier this year entitled, "Do We Have it All Wrong? ", we found that after accounting for family support, family conflict, peer support, and peer crime, our major assumptions about family and peers were completely in opposite direction as would currently be assumed (Mowen & Boman, 2019b). After accounting for the multifaceted roles of both family and peers among a sample of returning persons, we found that family conflict promoted crime while peer support reduced it!…”
Section: Empirical Studiesmentioning
confidence: 65%
“…Finally, the fourth question, which partially loaded onto family conflict, taps an emotional response while the remaining two items of family conflict capture actions (fighting and being criticized). Thus, this item captures a negative emotion probably more analogous to a lack of emotional support rather than family conflict, which could explain why family conflict has been shown to relate to reincarceration (Mowen and Boman 2018b). Collectively, this discussion demonstrates that family support measures are theoretically and methodological distinct.…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, accounting for family conflict as a separate measure to family support likely explains some of the differences in findings as well. Relatedly, factor analytic techniques demonstrated that one item used in prior research as a measure of family conflict (e.g., Mowen and Boman 2018b) was capturing negative emotions and not necessarily conflict. Again, these findings strongly suggest that researchers need to better consider the complexities and multidimensional nature of measures of family support and family conflict.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Largely defined as the receipt of tangible or intangible resources from social connections (Colvin, Cullen, & Vander Ven, 2002), social support is central to the reentry process. Existing research tends to highlight the importance of families (Bahr et al, 2010; Berg & Huebner, 2011; Mitchell, Spooner, Jia, & Zhang, 2016; Visher, 2004; Western, Braga, Davis, & Sirois, 2015) and peers (Bahr et al, 2010; Martinez & Abrams, 2013; Mowen & Boman, 2019) as sources of social support. These respective groups can provide important mechanisms of support including emotional (e.g., love and care) and instrumental (e.g., physical assistance such as housing and financial) support.…”
Section: Introductionmentioning
confidence: 99%